La representación apocalíptica de la violencia en la narrativa fílmica de Gabriel García Márquez: los guiones de El año de la peste y Edipo Alcalde, y los argumentos inéditos Dios y yo y Para Elisa. - Alessandro Rocco (Altre Modernità, 2013)
In Mario Vargas Llosa’s opinion, two of the most lasting obsessions of García Márquez’s literary world, were the theme of plague, and the one of violence, that together form a sort of “cataclysmic vision” of history, whose literary sources were Daniel Defoe’s, A journal of the plague year, and Sophocles’, Oedipus Rex. We mention in this article the presence of those themes in García Márquez’s filmic work, beginning with the screenplays of two films: El año de la peste and Edipo Alcalde, adaptations of the cited works of Defoe and Sophocles. Afterwards we present two unpublished film treatments, Para Elisa and Dios y yo. The first is about war in Colombia, and presents an explicit reference to the “Bogotazo” (9th of April of 1948), while the second presents the theme of Latin American dictator, that García Márquez later focused in his novel El otoño del patriarca.